MODELING OF THE PROCESS OF DISSOLVING OF POWDER CARBON CONTAINING MATERIALS OF VARIOUS BREAKUP IN MELT UNDER EFFECT OF ARGON - A. N. Chichko; N. V. Andrianov; S. V. Terletskij (Литьë и металлургия, 2004)
Modeling of the process of dissolving of powder carbon containing materials of various breakup in melt under effect of argon